A tornado over Orissa in April 1978 - GHOSH, ASHIM K. (MAUSAM, 1982)
An analytical study of a tornado which struck parts of districts Keonjhar and Cuttack in Orissa on 16 April 1978, causing large scale devastations of property and loss of human and animal lives, has been made. Synoptic situation responsible for its formation have been discussed.